Business Law and the Legal Environment - Mayer, Don; Warner, Daniel M.; Siedel, George J. (Open textbook library., 2012)
Our goal is to provide students with a textbook that is up to date and comprehensive in its coverage of legal and regulatory issues—and organized to permit instructors to tailor the materials to their particular approach. This book engages students by relating law to everyday events with which they are already familiar (or with which they are familiarizing themselves in other business courses) and by its clear, concise, and readable style. (An earlier business law text by authors Lieberman and Siedel was hailed “the best written text in a very crowded field.”) This textbook provides context and essential concepts across the entire range of legal issues with which managers and business executives must grapple. The text provides the vocabulary and legal acumen necessary for businesspeople to talk in an educated way to their customers, employees, suppliers, government officials—and to their own lawyers.